2021
DOI: 10.3390/en14217033
|View full text |Cite
|
Sign up to set email alerts
|

Review of Renewable Energy Potentials in Indonesia and Their Contribution to a 100% Renewable Electricity System

Abstract: Indonesia has an increasing electricity demand that is mostly met with fossil fuels. Although Indonesia plans to ramp up Renewable Energy Technologies (RET), implementation has been slow. This is unfortunate, as the RET potential in Indonesia might be higher than currently assumed given the archipelago’s size. However, there is no literature overview of RET potentials in Indonesia and to what extent they can meet current and future electricity demand coverage. This paper reviews contemporary literature on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
4

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(46 citation statements)
references
References 77 publications
0
42
0
4
Order By: Relevance
“…This places Indonesia in the tropics and beyond the equator. The average daily solar irradiation level is relatively high at 4.5 kWh/m 2 /day, and it has great potential for the development of solar power plants (PLTS) [15]- [17].…”
Section: Proposed Methods 21 Sun Energymentioning
confidence: 99%
“…This places Indonesia in the tropics and beyond the equator. The average daily solar irradiation level is relatively high at 4.5 kWh/m 2 /day, and it has great potential for the development of solar power plants (PLTS) [15]- [17].…”
Section: Proposed Methods 21 Sun Energymentioning
confidence: 99%
“…Energi terbarukan merupakan energi yang didapatkan dari sumber yang tidak terbatas, murah, bersih, efisiensi dan stabilitas tinggi diantaranya angin, panas matahari, panas bumi, aliran air, dan biomassa [3]. Salah satu pengaplikasian energi angin menggunakan turbin yang berputar, dimana mengubah energi mekanik menjadi energi listrik untuk digunakan pada pengecasan baterai dan pompa air.…”
Section: Pendahuluanunclassified
“…Still, so far, only limited articles are discussing the wind energy feasibility on Karimunjawa Island. However, Jannis Langer et al ( 2021), in a study on the potential of new and renewable energy in Indonesia, stated that at an average wind speed of 4 m/s to 6 m/s, every 100 kW of wind power requires an area of 0.25 km 2 [45].…”
Section: Wind Energy Potential In Karimunjawa Islandmentioning
confidence: 99%
“…This result means that the potential for wind energy on Karimunjawa Island is not feasible to build wind power plants. (3) Based on the findings in [45] , which are the motivation to find out the relationship between the wind power generated based on the area requirement, it can be concluded that the Karimunjawa Island area is 71.2 km 2 the wind energy density on Karimunjawa Island is 400 w/m 2 . This wind energy density is classified as "Good" [47] or ranked in the 4th [48,49], but the classification at the average wind speed is 7 m/s.…”
Section: Levelized Cost Of Electricity (Lcoe) and Electric Production...mentioning
confidence: 99%